Attitudes of Secondary School Students Towards Teaching Styles Before and During the COVID-19 Pandemic - Marijana Škutor (University of Maribor Press, 2023)
The aim of this paper was to examine students' attitudes towards teaching styles before and during the COVID-19 pandemic. Mean values were calculated using descriptive statistics, and the T-test for independent samples was used to determine the existence of statistically significant differences between groups. After testing the difference in student assessment of the teachers' style in two different school years, no statistically significant difference was found, potentially owing to student adaptation to the situation. A positive- sign correlation coefficient between the democratic and laissez-faire styles was recorded at a significance level of p<0.05.